2015
DOI: 10.1016/j.ejbas.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Preventing male infertility by marjoram and sage essential oils through modulating testicular lipid accumulation and androgens biosynthesis disruption in a rat model of dietary obesity

Abstract: Preventing male infertility by marjoram and sage essential oils through modulating testicular lipid accumulation and androgens biosynthesis disruption in a rat model of dietary obesity, Egyptian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…In contrast, a decline in weight, adiposity index, leptin and prolactin levels were observed. Likewise, sperm count and the testicular structure were comparable with that of the normal group [104]. In a related study, a synergistic action of OM and grape seed extract on reproductive function was evaluated by using ethanol to induce oxidative stress and reproductive disturbances.…”
Section: Herbal Remedy For Male Infertilitymentioning
confidence: 99%
“…In contrast, a decline in weight, adiposity index, leptin and prolactin levels were observed. Likewise, sperm count and the testicular structure were comparable with that of the normal group [104]. In a related study, a synergistic action of OM and grape seed extract on reproductive function was evaluated by using ethanol to induce oxidative stress and reproductive disturbances.…”
Section: Herbal Remedy For Male Infertilitymentioning
confidence: 99%
“…In this context, the administration of marjoram to coragentreated rats was functioning in adjusting the plasma levels of sex hormones to a considerable degree. El-Wakf et al [37] reported a similar increase in the testosterone hormone level by marjoram that could be attributed to the direct effect of marjoram extracts on the hypothalamus-pituitary-testis axis. Furthermore, they demonstrated that marjoram is a rich source of terpenoids, asthymol, carvacrol, 4-terpineol, γ-terpinene, αterpinene.…”
Section: Discussionmentioning
confidence: 84%
“…He suggested that the water extract of marjoram had a therapeutic and chelating effect against cadmiuminduced nephrotoxicity [36] . Previous study indicated that marjoram essential oils had a considerable free radical scavenging activity, thus protecting the organs of the body from injury associated with dietary obesity [37] . The synthetic compounds or drugs are often tried to overcome the infertility problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations